Sesame oil in diets for lambari: Effects on growth parameters, corporal chemical composition and physiological alterations - Natori,Mariene Miyoko (2016)
ABSTRACT: The inclusion of sesame oil associated with soybean, linseed and freshwater fish residue oil in the diets fed to Lambaris Astyanax altiparanaewas evaluated by the growth performance parameters, body composition and possible physiological changes (GARUTTI & BRISTSKI, 2000). The experiment was a completely randomized design in two factorial parameters tested: three oil types (soy oil (SO), linseed oil (LO) and freshwater fish residue oil (FRO)), combined or not with sesame oil (SEO), totalizing six treatments and four replications 24 cages, capacity of 0.70m3 (density of 251 fish m-3). The fish (mean weight 2.35g±0.62g and mean length 5.25cm±0.68cm) were fed with the experimental diets twice a day. After 75 days, the following parameters were determined: body chemical composition and fatty acid profile, glycemia, liver (LG) and muscle glycogen (MG) levels, and lipid peroxidation (TBARS). Fish fed with diets containing SEO had higher desaturation index values of LNA while those fed with SEO combined with LO displayed reduced hepatic lipid oxidation. Inclusion of SEO improved the fatty acid profile and stability, without causing problems related to fish performance and health.